Three Years of Experience with QuantiFERON-TB Gold Testing in Patients with Uveitis. (December 2014) - Jakob, E.; Max, R.; Zimmermann, S.; Dalpke, A. H.; Alle, W.; Becker, M.; Mackensen, F.
Abstract Purpose: Overview of the results of QuantiFERON-TB Gold (QFT) testing on uveitis patients in an interdisciplinary setting for a period of 3 years. Methods: Database search of all the patients tested for tuberculosis (Tb) with QFT. Results: Of 343 tested patients, overall 80 (23.3%) were positive and 253 (73.8%) negative (results were nonconclusive for 10 patients). Anatomic localization of the patients who tested positive were distributed (% of QFT+ tests) as anterior n = 12 (15.0%), intermediate n = 22 (27.5%), posterior n = 26 (32.5%), and pan n = 18 (22.5%). In 43 QFT+ patients we presumed a diagnosis of Tb due to additional clinical findings. Of these patients 16 were treated with full therapy following WHO recommendations. Conclusions: QFT testing gives surprisingly high numbers of positives in uveitis patients. This is not sufficiently explained by immigrant status of the patients. The frequency of positives is substantially higher than in other cohorts. This raises important questions regarding treatment implications.